Editorial - María Claudia Nieto Cruz; Melba Libia Cárdenas (Universidad Nacional de Colombia, 2016)
As always, we hope our journal reaches a wide range of educators. We also hope the communities of our readers can benefit from the contributions of authors from Brazil, Colombia, Mexico, the United States, and Turkey. We acknowledge the rigor of their works and look forward to more manuscripts in the areas they have addressed in their articles as well as in others that are embraced in the mission of our publication.